2022
DOI: 10.3390/su14116854
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal and Small-Scale Gold Mining (ASGM): Management and Socioenvironmental Impacts in the Northern Amazon of Ecuador

Abstract: Mining is one of the oldest economic activities of mankind. Within this activity, artisanal and small-scale gold mining (ASGM) is one of the most studied sectors due to its high level of environmental contamination and the social problems it causes. In recent years, ASGM in the northern Amazon of Ecuador has increased significantly, and studies that describe its current situation and impact are scarce. In this sense, the present study aimed to analyze the current status and socioenvironmental impacts caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 78 publications
0
12
0
1
Order By: Relevance
“…Several studies have reported the presence of various anthropogenic sources of contamination in the Ecuadorian Amazon, which can affect water quality, both surface and groundwater; among the main ones are artisanal and small-scale gold mining (mainly carried out illegally), inadequate management of mining environmental liabilities [ 5 ], fish farming [ 20 ], and natural Hg leaching from deforestation [ 37 ]. Therefore, assessing water quality in these environments is essential to ensure the protection of water resources and, thus, the safety of users.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the presence of various anthropogenic sources of contamination in the Ecuadorian Amazon, which can affect water quality, both surface and groundwater; among the main ones are artisanal and small-scale gold mining (mainly carried out illegally), inadequate management of mining environmental liabilities [ 5 ], fish farming [ 20 ], and natural Hg leaching from deforestation [ 37 ]. Therefore, assessing water quality in these environments is essential to ensure the protection of water resources and, thus, the safety of users.…”
Section: Resultsmentioning
confidence: 99%
“…In its beginnings, mining was carried out with rudimentary techniques; in the last decades, an important enhancement of the methods used, which vary from place to place, has been recorded. It can be carried out at different scales and in different ways; it often continues to be carried out illegally or informally, and in some cases, local authorities tend to tolerate it [ 5 ]. Currently, medium- and large-scale mining projects have developed and consolidated alongside artisanal and small-scale activities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The name of this region is derived from the major rivers that flow through it, namely the Kuantan River and the Singingi River. The accumulation of alluvial sediments containing goldbearing materials has attracted miners to exploit these minerals [10]. The exploration of gold-bearing materials in Kuantan Singingi began in 2005 and has continued to accelerate up to the present day [11].…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, the exploitation of forest resources contributes substantially to the environmental degradation of the Amazon, with small-scale mining playing a crucial role in countries such as Suriname, Ecuador, Peru, and Guyana [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%